2017
DOI: 10.2134/itsrj2016.05.0359
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation and Control of Annual Bluegrass Resistant to Photosystem‐II‐Inhibiting Herbicides

Abstract: An annual bluegrass (Poa annua L.) phenotype suspected to be resistant to photosystem II (PSII)‐inhibiting herbicides was identified in a zoysiagrass [Zoysia matrella (L.) Merr., cv. ‘Royal’] sod production field during 2013. Research was conducted during 2013 to 2015 to confirm if this phenotype (R) was resistant to PSII‐inhibiting herbicides and evaluate alternative herbicide options for effective preemergence control. In the glasshouse, treatment with the PSII‐inhibiting herbicide simazine at the maximum la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…For example, PRE applications of indaziflam at 52.5 to 70 g ha −1 controlled dinitroaniline‐resistant annual bluegrass 88–97% rated 180 days after treatment (DAT) . Similar responses have been reported following PRE applications of indaziflam to control annual bluegrass with resistance to acetolactate synthase (ALS) and photosystem II (PSII) inhibiting herbicides …”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, PRE applications of indaziflam at 52.5 to 70 g ha −1 controlled dinitroaniline‐resistant annual bluegrass 88–97% rated 180 days after treatment (DAT) . Similar responses have been reported following PRE applications of indaziflam to control annual bluegrass with resistance to acetolactate synthase (ALS) and photosystem II (PSII) inhibiting herbicides …”
Section: Introductionmentioning
confidence: 67%
“…This is a first report of annual bluegrass resistance to indaziflam applied early‐postemergence. Evolution of annual bluegrass with resistance to indaziflam is concerning given that the herbicide is an important tool for turfgrass managers controlling annual bluegrass with resistance to mitotic inhibitor, PSII‐, and ALS‐inhibiting herbicides . The scope of multiple resistance documented herein is perhaps more concerning given that annual bluegrass surviving EPOST treatment with indaziflam was also able to survive EPOST treatment with six other modes of action.…”
Section: Discussionmentioning
confidence: 93%
“…For example, Hutto et al (2004) identified simazine-resistant annual bluegrass on 43% of golf courses in Mississippi. Simazine resistance was also identified in annual bluegrass on a sod farm in Tennessee (Brosnan et al 2017b), which could perpetuate the issue over a wider geographical area. Moreover, annual bluegrass with multiple resistance to PSII inhibitors and other SOAs, particularly ALS inhibitors, has been reported (Brosnan et al 2015(Brosnan et al , 2016.…”
Section: Photosystem II (Psii)-inhibitor Resistance In Turfgrass (Wssmentioning
confidence: 99%
“…In turfgrass, FreeHand effectively controlled simazine (6‐chloro‐2‐ N ,4‐ N ‐diethyl‐1,3,5‐triazine‐2,4‐diamine)‐resistant ABG when applied preemergence in a zoysiagrass ( Zoysia spp.) sod production field (Brosnan, Breeden, Vargas, & Grier, 2017).…”
Section: Chemical Control Of Annual Bluegrassmentioning
confidence: 99%
“…A survey of ABG populations on 90 golf courses in Tennessee (representing 30% of the 297 courses in the state) revealed sizeable percentages of ABG that was resistant to glyphosate (64%), foramsulfuron (21%), prodiamine (58%), or simazine (97%) (Brosnan, Vargas, Breeden, & Zobel, 2020a). Several researchers have demonstrated that herbicide mixtures with several modes of action can be useful in managing herbicide‐resistant grassy weeds (Breeden et al., 2017; Brosnan et al., 2017; Busi, Powles, Beckie, & Renton, 2019).…”
Section: Chemical Control Of Annual Bluegrassmentioning
confidence: 99%